2011
DOI: 10.1007/s12665-011-1341-0
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Cd, Zn and Pb in sewage sludge using red mud

Abstract: Sewage sludge is an inevitable end by-product of sewage treatment. Land application provides a costeffective alternative for sewage sludge disposal. However, sewage sludge contains heavy metals that may limit its application. In this work, red mud was employed for the immobilization of heavy metals in sewage sludge. The effect of red mud amendment on heavy metal immobilization was evaluated using Toxicity Characteristic Leaching Procedure (TCLP) method. The TCLP results showed that the immobilization efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Liang et al [119] used red mud and lime to immobilize heavy metals in sewage sludge, and found that the two amendments at 10% could significantly reduced the water extractable heavy metals, which was comparable with that at 15% of red mud or lime. Red mud is a kind of mixture that is composed of TiO 2 , a certain amount of dicalcium phosphate, and amorphous aluminosilicate materials.…”
Section: Synergistic Effects Of Different Immobilizing Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Liang et al [119] used red mud and lime to immobilize heavy metals in sewage sludge, and found that the two amendments at 10% could significantly reduced the water extractable heavy metals, which was comparable with that at 15% of red mud or lime. Red mud is a kind of mixture that is composed of TiO 2 , a certain amount of dicalcium phosphate, and amorphous aluminosilicate materials.…”
Section: Synergistic Effects Of Different Immobilizing Methodsmentioning
confidence: 97%
“…XRD and SEM analysis showed that there was no detectable changes in the mineralogy of sewage sludge after chemical amendment by 10% red mud. Liang et al [119] selected 10% red mud to mix with sewage sludge, and found that the immobilization efficiency of Cd, Zn, and Pb was 100%, 92%, and 82%, and their plant available was reduced from 18.13%, 17.22%, and 13.64% to 6.98%, 11.36%, and 7.12%, respectively.…”
Section: Red Mudmentioning
confidence: 99%
“…In contrast, Pb concentrations in soil solution decreased with amendment addition. Redmud was shown to be efficient to immobilize metallic elements in several studies (Gray, Dunham, Dennis, Zhao, & McGrath, 2006;Liang, Peng, & Luan, 2012). Such positive effect can be attributed to the high content of Fe and Al oxides, which can complex metals (Gray et al, 2006;Jenne, 1968;Liang et al, 2012).…”
Section: Spw Physico-chemical Propertiesmentioning
confidence: 99%
“…In our study, alkaline amendments (A and B) composed of CaO had significant positive effects on the decrease of soil Acd, which can be probably due to pH value. A large number of studies (68, 69) have shown that soil pH is a very important factor affecting available heavy metal concentration, controlling the adsorption-desorption of heavy metals in soil and the chemical behaviors such as dissolution-deposition. And alkaline amendments also had a favorable impact on taxonomic and functional patterns, especially on microbial diversity, soil nitrogen fixation and the growth of related bacteria, which conducive to the decrease of soil Acd.…”
Section: Discussionmentioning
confidence: 99%